POLA PENGAMBILAN KEPUTUSAN MORAL KELOMPOK MAHASISWA LPTK DALAM LINGKUP MORALITAS SOSIOKULTURAL PADA ERA GLOBALISASI - Suparlan Al Hakim (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2012)
Problems dealing with concepts and application about values, moral, attitudes, consideration, and decision makingby college students are interesting subjects. It is especially for educators, scholars, community leaders, and parents. Nowadays, teenagers do not have enough staying power and precise moral consideration in decision making. It includes decision making not only private decision, but also group decision. The goals of this writing are to describe types of sociocultural moralities evolving in college studenls' lives; describe moral problematics or moral dilemma faced by college students; describe pattems of decision making by college students using the sociocultural morality reference; describe types of sociocultural morality evolving in college students lives based on moral development theory by Kohlberg.